2010
DOI: 10.1016/s0828-282x(10)70355-x
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Cardiovascular Society 2009 Consensus Conference on the management of adults with congenital heart disease: Outflow tract obstruction, coarctation of the aorta, tetralogy of Fallot, Ebstein anomaly and Marfan's syndrome

Abstract: With advances in pediatric cardiology and cardiac surgery, the population of adults with congenital heart disease (CHD) has increased. In the current era, there are more adults with CHD than children. This population has many unique issues and needs. Since the 2001 Canadian Cardiovascular Society Consensus Conference report on the management of adults with CHD, there have been significant advances in the field of adult CHD. Therefore, new clinical guidelines have been written by Canadian adult CHD physicians i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
131
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 188 publications
(136 citation statements)
references
References 178 publications
(135 reference statements)
1
131
0
4
Order By: Relevance
“…42,43 The Canadian guidelines state that a peak instantaneous LVOT gradient >50 mm Hg is an indication for reoperation when patients have symptoms. 44 The timing of reoperation is a highly complex issue that should take various factors into account: the peak LVOT gradient, progression rate of the LVOT gradient, severity and progression of AR, left ventricular volume and function, presence of (exercised-induced) symptoms, and risk of sudden death. Unfortunately, the optimal timing of reoperation, when all these factors are combined, in adult patients with DSS cannot yet be derived from the present study.…”
Section: Study Limitationsmentioning
confidence: 99%
“…42,43 The Canadian guidelines state that a peak instantaneous LVOT gradient >50 mm Hg is an indication for reoperation when patients have symptoms. 44 The timing of reoperation is a highly complex issue that should take various factors into account: the peak LVOT gradient, progression rate of the LVOT gradient, severity and progression of AR, left ventricular volume and function, presence of (exercised-induced) symptoms, and risk of sudden death. Unfortunately, the optimal timing of reoperation, when all these factors are combined, in adult patients with DSS cannot yet be derived from the present study.…”
Section: Study Limitationsmentioning
confidence: 99%
“…The present result differs from the findings of the relatively large prospective study by Meijboom et al, in which it was concluded that pregnancy in women with Marfan syndrome seems to be relatively safe up to an aortic root diameter of 45 mm, 15 and from Canadian guidelines that recommend that women with an aortic root diameter beyond 44 mm should be strongly discouraged from becoming pregnant. 24 Taking into account that Japanese women have a generally smaller physique than European and North American women, we recommend that the cut-off for Japanese patients for advice regarding avoidance of pregnancy should be a sinus of Valsalva diameter ≥40 mm, rather than ≥45 mm. In a case report on a patient who developed a massive retrograde type B aortic dissection 7 days after normal spontaneous vaginal delivery, Gandhi et al described the patient as "petite" (body surface area, 1.69 m 2 ), but this is still larger than the average Japanese woman.…”
Section: Discussionmentioning
confidence: 99%
“…Specific cardiac recommendations include education on the maternal and fetal risks, contraception advice, pre-pregnancy optimisation of blood pressure, modification of fetotoxic medications, interventions to optimise pregnancy outcomes and, when appropriate, the potential late effect of pregnancy on the heart as well as maternal life expectancy. [2][3][4][5] Counselling should also include a detailed obstetric history, including an assessment of the risk of complications such as pre-eclampsia that might impact on cardiovascular function. Pre-eclampsia may cause an increase in afterload and potential deterioration in cardiac function.…”
Section: Preconception Counsellingmentioning
confidence: 99%
“…Specific cardiac recommendations include education on the maternal and fetal risks, contraception advice, pre-pregnancy optimisation of blood pressure, modification of fetotoxic medications, interventions to optimise pregnancy outcomes and, when appropriate, the potential late effect of pregnancy on the heart as well as maternal life expectancy. [2][3][4][5] …”
mentioning
confidence: 99%